O Colégio Pedro Gomes entre projetos de modernidade e práticas educacionais subjetivas: uma perspectiva a partir das memórias de Lígia Rebelo (1956-1966) - Machado, Vinícius Felipe Leal (2025)
Founded in 1947, “Colégio Estadual Professor Pedro Gomes”, also known as “CEPPG”, was the first public secondary education institution (equivalent to high schools) in the neighborhood, of Campinas, the old city from which Goiânia originated. Lígia Maria Coelho Rebelo was the school principal, in this institution, between 1956 and 1966. The implementation of the then “Ginásio Estadual de Campinas” (an elementary state school, the previous form of CEPPG), in 1950, represented a paradigmatic element of modernization that impacted the region, leading, in the following years, to sociopolitical developments that culminated in the main expansion that occurred in the history of the institution, in 1960. Under the leadership of Lígia Rebelo, “Colégio Pedro Gomes” established a substantial part of its material and symbolic foundations that would lead it to achieve a position of great visibility and prestige within the group of public schools in the State of Goiás. The thesis supported by this work is that Lígia Rebelo's management was responsible for conducting administrative and political-pedagogical processes – subjective educational practices – that reflected, within the school, the external processes of socioeconomic modernization promoted by the government, in Goiás and in the country as a whole. So, we discuss the interrelationship between this processes, that resulted in the expansion of infrastructure and the broadening of the scope of educational activities offered and the conduction of subjective educational practices that contributed to the construction and consolidation of the school culture and the institutional identity of the school. In this sense, this work analyzes the implementation of the project that gave rise to the school's marching band and the political-educational dimensions acquired by the student union. Based on the analysis of institutional documents, publications in periodicals, like newspapers of that time, besides documents from Lígia Rebelo's personal memoir archive, this research investigates the hypothesis that the director was successful in the roles of educator and bureaucrat, thereby managing to benefit from a network of political contacts that guaranteed her a favorable position in society, extending it to the institution under her tutelage. Thus, Lígia Rebelo established the merit of having been the professional who remained the longest in the role of principal of that school, managing to attribute to the period in which she was in charge of CEPPG, a valuable symbolic charge related to the idea of a “golden moment”: what would have been, until then, the greatest qualitative leap towards the modernization of public education offered to the community of Campinas. From this perspective, the memorialist practices established by Lígia Rebelo, in private or public records, serve her personal purpose of perpetuating, in the collective imagination, her link with this “mythical moment” in the History of Colégio Pedro Gomes, while at the same time revealing a latent need for the government to incorporate educational spaces in the support of projects of authority and power.